The Autonomous Industrial Plant -Future of Process Engineering, Operations and Maintenance. Issue 1 (2019) - Gamer, Thomas; Hoernicke, Mario; Kloepper, Benjamin; Bauer, Reinhard; Isaksson, Alf J.
Abstract: Almost every day we read about new advances in self-driving cars and artificial intelligence. For autonomous driving, there already exist established standards with six levels describing the steps from driving without assistance to fully automated, i.e., autonomous driving. While many people and industries - in particular the automotive industry - believe that self-driving cars are feasible in the near future, one may ask how feasible full autonomy is in the process industry? Is it realistic to aim towards a fully autonomous chemical plant, and what does full autonomy even mean for the process industries? This paper introduces a definition of autonomy and corresponding levels of autonomy for the process industry. We start from an abstract definition of six autonomy levels that are applicable to various industrial domains, also illustrated by recent examples from different industrial applications such as mining or marine. Then, we discuss the applicability of this definition for process industry in a first step. In a second step of refinement, we also study some key autonomous features of process operations and give examples for the meaning of each autonomy level per feature.